CROSS-CULTURAL FRIENDSHIP IN THE DIGITAL ERA: OPPORTUNITIES AND CHALLENGES - Baiti Nabila Sari; Mariana Efrasia Dade; Meliana; Nurfaizah Sahib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has transformed the way people communicate and build relationships across cultural boundaries. Through social media, online communities, and virtual communication platforms, individuals can establish and maintain cross-cultural friendships more easily than ever before. These friendships provide opportunities for cultural exchange, the development of intercultural competence, English language practice, and global networking. However, they also present challenges, including language barriers, cultural misunderstandings, stereotypes, differences in communication styles, and the limitations of digital communication. This article discusses both the opportunities and challenges of cross-cultural friendship in the digital era by drawing on recent literature in intercultural communication and English language education. The discussion highlights the importance of intercultural awareness, empathy, mutual respect, and responsible digital communication in fostering meaningful intercultural relationships. Furthermore, the article emphasizes the role of cross-cultural friendship in supporting English as a Foreign Language (EFL) students’ language development and intercultural competence. It concludes that meaningful cross-cultural friendships can contribute to greater global understanding and prepare students to participate effectively in multicultural academic and professional environments.